Zoonotic tuberculosis in human beings caused by Mycobacterium bovis—a call for action. Issue 1 (January 2017) - Olea-Popelka, Francisco; Muwonge, Adrian; Perera, Alejandro; Dean, Anna S; Mumford, Elizabeth; Erlacher-Vindel, Elisabeth; Forcella, Simona; Silk, Benjamin J; Ditiu, Lucica; El Idrissi, Ahmed; Raviglione, Mario; Cosivi, Ottorino; et al.
Summary: Mycobacterium tuberculosis is recognised as the primary cause of human tuberculosis worldwide. However, substantial evidence suggests that the burden of Mycobacterium bovis, the cause of bovine tuberculosis, might be underestimated in human beings as the cause of zoonotic tuberculosis. In 2013, results from a systematic review and meta-analysis of global zoonotic tuberculosis showed that the same challenges and concerns expressed 15 years ago remain valid. These challenges faced by people with zoonotic tuberculosis might not be proportional to the scientific attention and resources allocated in recent years to other diseases. The burden of zoonotic tuberculosis in people needs important reassessment, especially in areas where bovine tuberculosis is endemic and where people live in conditions that favour direct contact with infected animals or animal products. As countries move towards detecting the 3 million tuberculosis cases estimated to be missed annually, and in view of WHO's end TB strategy endorsed by the health authorities of WHO Member States in 2014 to achieve a world free of tuberculosis by 2035, we call on all tuberculosis stakeholders to act to accurately diagnose and treat tuberculosis caused by M bovis in human beings.